SUPERVISI KEPALA SEKOLAH TERHADAP KEDISIPLINAN DAN KINERJA GURU DI SMP AL-WASHLIYAH 26 MEDAN - Nispi Ani Barus; Nispi Ana Barus; Muhammad Irsan Barus (Prodi Pendidikan Agama Islam STAIN Mandailing Natal, 2020)
This research aims to explore the training and teacher performance by headmaster supervision program.The research approach of this study uses qualitative research with using phenomenology approach.The headmaster of Junior High School in SMP al washlyah 26 marelan has the best planning program and concrete indicator in performing his function as an supervisor.The teacher performance is good enough during teaching and learning process. It can be seen from learning standard that was done. Teacher training is built by the headmaster using active communication so that it can improve the relationship of the head master and the others teacher being good relationship.